Acute pancreatitis in children: a tertiary hospital report - Antunes, Henedina (2014)
INTRODUCTION: The incidence of acute pancreatitis (AP) in children has increased significantly in the past two decades. OBJECTIVE: All cases of AP, acute recurrent pancreatitis (ARP), and chronic pancreatitis examined between May 2002 and May 2012 at Hospital de Braga, Portugal, were reviewed. MATERIAL AND METHODS: Patients were identified by searching the hospital's electronic discharge records for the International Classification of Disease, Ninth Revision (ICD-9) code 577.0 (acute pancreatitis). ARP was considered as two or more episodes of AP per year or more than three episodes over a lifetime with intervening return to baseline. The following data were analyzed: demographic information, clinical, laboratory and imaging test results, etiology of pancreatitis, medical and surgical management, length of hospitalization, and outcome. The clinical and laboratory factors used in the pediatric acute pancreatitis severity score system and computed tomography severity index (CTSI) score were compared between patients with mild and severe disease. RESULTS: A total of 37 patients, 31 episodes of AP and 6 patients with ARP, were documented. The most prevalent etiologies were biliary stones/sludge (24.3%) and trauma (16.2%). Admission elevated white blood cell count (p=0.011), 48-h trough calcium (p=0.007), and 48-h rise in blood urea nitrogen (p=0.025) correlated significantly with disease severity. CTSI on admission had a score below 4 in three patients with severe disease. CONCLUSION: This Portuguese pediatric pancreatitis report highlights the multiple and complex etiology of this disease. Better pediatric scoring systems and management algorithms are needed.